2020
DOI: 10.3390/ijms21041536
|View full text |Cite
|
Sign up to set email alerts
|

A microRNA Expression Profile as Non-Invasive Biomarker in a Large Arrhythmogenic Cardiomyopathy Cohort

Abstract: Arrhythmogenic Cardiomyopathy (AC) is a clinically and genetically heterogeneous myocardial disease. Half of AC patients harbour private desmosomal gene variants. Although microRNAs (miRNAs) have emerged as key regulator molecules in cardiovascular diseases and their involvement, correlated to phenotypic variability or to non-invasive biomarkers, has been advanced also in AC, no data are available in larger disease cohorts. Here, we propose the largest AC cohort unbiased by technical and biological factors. Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…Miravirsen is a locked nucleic acid-modified DNA phosphorothioate antisense oligonucleotide that sequesters mature miR-122 in a highly stable heteroduplex, thereby inhibiting its function. Bueno Marinas et al [ 30 ] observed that miR-122-5p was underexpressed in tissue and overexpressed in the circulation, supporting the hypothesis that the high blood levels of miRNAs might be released from apoptotic or necrotic cardiomyocytes, indicating progression of tissue damage. They indicated that myocardial damage is reflected in the circulation and that these miRNAs can be used as noninvasive biomarkers of the disease, permitting differential diagnosis.…”
Section: Discussionmentioning
confidence: 91%
“…Miravirsen is a locked nucleic acid-modified DNA phosphorothioate antisense oligonucleotide that sequesters mature miR-122 in a highly stable heteroduplex, thereby inhibiting its function. Bueno Marinas et al [ 30 ] observed that miR-122-5p was underexpressed in tissue and overexpressed in the circulation, supporting the hypothesis that the high blood levels of miRNAs might be released from apoptotic or necrotic cardiomyocytes, indicating progression of tissue damage. They indicated that myocardial damage is reflected in the circulation and that these miRNAs can be used as noninvasive biomarkers of the disease, permitting differential diagnosis.…”
Section: Discussionmentioning
confidence: 91%
“…Of these, 11 miRNA transcripts were validated by qRT-PCR (Figs 5 and 6 ), and 8 of these 11 have been previously linked to human AMI {miR-1 [ 23 ]; miR-133 [ 23 , 24 ]; miR-146a [ 28 , 29 ]; miR-208b [ 23 ]; miR-335 [ 30 ]; miR-423 [ 24 ]; miR-483 [ 31 ] and miR-499 [ 27 ]}. In contrast, only 5 miRNAs showed a significantly increased concentration in CS when compared to AMI serum samples ( Table 3 ), of which 3 have been linked to myocardial disease {miR-144 (validated, Fig 6 ) [ 32 , 33 ], miR-624a and miR-624b [ 34 , 35 ]}.…”
Section: Resultsmentioning
confidence: 99%
“…Even though each group showed some of these miRNAs DE, only AC definite patients shared this unique 6-miRNA profile (AUC 0.995 AC definite vs. ctrl; >0.82 AC definite vs. validation cohorts) which support its role as non-invasive biomarker. In silico predictions showed a clear correlation of this 6-miRNA profile to AC-related signaling pathways but functional studies are needed to determine its role in disease pathogenesis [ 66 ].…”
Section: Micrornas In Ac Human Samplesmentioning
confidence: 99%